Botanical composition, nutritional status and carrying capacity of native alpine pasture of Bara Bangahal for sheep - DOGRA, K K; KATOCH, B S; SINGH, B (The Indian Journal of Animal Sciences, 2013)
Grazing lands of alpine pastures of Bara Bangahal (above 3 170 m msl, Kangra, H.P.) were evaluated for their botanical composition, nutritional staws and carrying capacity. Agroslis stoionifera. Dactylis glomerata. Andropogon ischaemum and Agropyron spp. provided about 700/0 cover. CP, cell solubles and Ca were high)n August and declined in September. NDF, ADF and lignin increased with maturity. Trace mineral status was adequate except copper. Sheep (60 and 30 days trial) gained 18.33 g/day and DMI was 3.73 kg/100 kg b:w. A low carrying capacity of 2 sheep/ha annum was observed. There is a tremendous scope for the introduction of improved species.